Hierarchical economic information filtering model concerning vendor selection. (16th February 2011) - Shu, Tong; Chen, Shou; Chao, Xiuli; Lai, Kin Keung
This paper proposes a new hierarchical economic information filtering model for vendor selection, consisting of three phases in which leading enterprises select their vendors, namely, the phase of collecting and releasing information, the phase of selecting vendors and the phase of dynamic rating of vendors. Rating and search criteria are different for the three levels of search. It analyses the weights for individual criteria and their relative importance in accordance with the hierarchical economic information filtering model, multiple rounds of feedback from the management staff in manufacturing industries and the method of analytical hierarchy process. Hierarchical economic information filtering model defines the information search criteria of vendor selection, which contributes to increasing information search efficiency, and reduces information search time and cost. Also, vendor information can be dynamically filtered, selected, treated and responded to real time. The establishment and application of this model can help to define tasks and foci in relation to selection and rating of vendors in varying phases. It might help leading enterprises to accommodate vendors dynamically in terms of the rating results, and avoid noisy information and data when selecting and rating vendors in different phases. It can be considered as an extension of filtering economic information in varying phases and modules.